Variation of soil properties under different land use systems in mid-hills of Nepal - Bhusal, Subash Chandra; Pande, Keshab Raj; Shriwastav, Chandeshwar Prasad; Adhikari, Anu (Journal of Experimental Sciences, 2024)
This research was conducted in four VDCs of Darechok from Chitwan, Sarangkot from Kaski, Tilhar from Parbat and Bhatkhola from Syangja including two components of field research survey and soil sampling in 2014/2015 to determine soil properties in different land use systems in relation to soil erosion and landslide. This was designed as a factor randomized complete block design with six treatments and land use systems replicated four times. There were six types of predominant land use systems namely perennial orchard, forest, maize based, vegetable based, fallow and rice based lands. Among different districts, soil of Kaski was loamy and that of Chitwan, Parbat and Syangja was sandy loam. Among the treatments, maize based system has the highest bulk density as compared to soils from other cropping systems while moisture percentage was the highest in rice based land use systems. The highest pH (6.02) in maize based agricultural land and that of the lowest (4.6) in forestland systems were observed. The highest organic matter (5.95 %) and nitrogen content (0.3050%) were in forests. Phosphorus was found significantly higher (98.25 kg/ha) in vegetable land. There was a positive correlation (R2=0.5381) between nitrogen and organic matter content and organic matter content and phosphorus content (R2=0.1026). The highest value of potassium (312 kg/ha) was detected in soils from maize based systems. Among different land use systems, forestland contains relatively higher amounts of nutrients than others. From both the risk factors and soil fertility point of view forest land use systems were the best among the treatments.